Study on the spatial planning of the secondary station: Located areas along Chinese Eastern Railway - Zhang, Bocheng; Zhao, Zhiqing; Wang, Qinglian (International Planning History Society Proceedings, 2018)
During the Chinese Eastern Railway construction (1897-1903), a large amount of areas attached to railway station-located areas had been constructed and developed constantly, which therefore facilities the emergence of new type morphology of cluster arising from the railway in northeast China. And the towns’ morphology of this period had had the profound influence on the subsequent the towns’ development in northeast China. In this research, the author himself went to St. Petersburg in Russia and to check and collect files in Russian National History Archives, from which a large amount of basic files about city construction during the period of the construction of Chinese Eastern Railway have been generated; then, based on the above materials (ages and number), the research period (construction of Chinese Eastern Railway 1897-1903) , objects (railway stations along the main lines of Chinese Eastern Railway:) and sample (Station Hailar and Suifenhe )are determined; Thirdly, the historic planning drawings and towns’ construction for two stations are translated to extract the planning information ,earlier city construction, social economy development , location features, land layout, texture of street profile, street transport, buildings’ texture, landscape greening and other basic elements of towns’ morphology. Two towns are compared to conclude the typical structural pattern and morphology. Ultimately, Russian style station in Suifenhe City is taken to conduct field research and empirical analysis and explicit the conservation content of historic features as well as propose the conservation ides depending on the principles of completeness and authenticity. After hundreds of years, the Russian style stations during the Chinese Eastern Railway have developed into to the commercial centers, which dominate in the modern city. Although the features of earlier Russian style stations have been broken, these centers still demonstrate strong sense of environment and landscape as Russian style colonial city. This research intends to explore the planning content of earlier stations to restores the planning elements of earlier cities with the ultimate aim to reveal the historical landscape of the towns, which is greatly significant to the conservation of urban historical features.